Relasi Politik, Bullying dan Etika Mengenai Isu “Muslim Uighur” di Media sosial - Yofiendi Indah Indainanto (UMSU, 2020)
AbstractThis study analyzes how the practice of political relations, cyberbullying and ethics in responding to Uighur Muslim issues through six posts that show attitudes and explanations on Twitter account Mahfud MD. The research method used is descriptive qualitative, with a virtual ethnographic approach. The results of the study show that the conversation in Twitter comments starts with the opinion leaders raising influencers in every comment about the issue of discrimination against Uighur Muslims. The development of interaction becomes a place to attack Mahfud MD's personal by eliminating the main problems. Interaction of comments leads to the assessment of different attitudes between political elites who are not assertive, on the fear factor, and the existence of power relations outside religious issues. Poor social media ethics that act as commentary interactions do not create understanding and understanding of the issue. As a result, bullying has often taken place under comments dominated by avatar and anonymous accounts.Keywords: Virtual Ethnography, Social Media, Muslim Uighurs, Cyberbullying, Media EthicsAbstrakPenelitian ini menganalisis, bagaimana praktek relasi politik, cyberbullying dan etika dalam menanggapi isu muslim Uighur melalui enam postingan yang menunjukan sikap dan penjelasan diakun Twitter Mahfud MD. Metode penelitian yang digunakan adalah deskriptif kualitatif, dengan pendekatan etnografi virtual. Hasil penelitian menunjukan perbincangan dalam komentar twitter dimulai dari opinion leaders memunculkan influencer dalam setiap komentar terhadap isu diskriminasi muslim Uighur. Perkembangan interkasi justru menjadi ajang menyerang personal Mahfud MD dengan menghilangkan permasalahan utama. Interaksi komentar mengarah pada penilaian sikap berbeda pandangan antara elit politik yang tidak tegas,pada faktor ketakutan, dan adanya relasi kuasa diluar isu agama. Etika bermedia sosial yang buruk menjadi penyebap interaksi komentar tidak menimbulkan pengertian dan pemahaman tentang isu. Akibatnnya aksi bullying banyak terjadi dikolong komentar dengan didominasi menggunakan akun avatar dan anonim. Kata Kunci: Etnografi Virtual , Media Sosial, Muslim Uighur, Cyberbullying, Etika Media